PEG-Free Polyion Complex Nanocarriers for Brain-Derived Neurotrophic Factor - James M. Fay; Chaemin Lim; Anna Finkelstein; Elena V. Batrakova; Alexander V. Kabanov (MDPI AG, 2022)
Many therapeutic formulations incorporate poly(ethylene glycol) (PEG) as a stealth component to minimize early clearance. However, PEG is immunogenic and susceptible to accelerated clearance after multiple administrations. Here, we present two novel reformulations of a polyion complex (PIC), originally composed of poly(ethylene glycol)113-b-poly(glutamic acid)50 (PEG-PLE) and brain-derived neurotrophic factor (BDNF), termed Nano-BDNF (Nano-BDNF PEG-PLE). We replace the PEG based block copolymer with two new polymers, poly(sarcosine)127-b-poly(glutamic acid)50 (PSR-PLE) and poly(methyl-2-oxazolines)38-b-poly(oxazolepropanoic acid)27-b-poly(methyl-2-oxazoline)38 (PMeOx-PPaOx-PMeOx), which are driven to association with BDNF via electrostatic interactions and hydrogen bonding to form a PIC. Formulation using a microfluidic mixer yields small and narrowly disperse nanoparticles which associate following similar principles. Additionally, we demonstrate that encapsulation does not inhibit access by the receptor kinase, which affects BDNF's physiologic benefits. Finally, we investigate the formation of nascent nanoparticles through a series of characterization experiments and isothermal titration experiments which show the effects of pH in the context of particle self-assembly. Our findings indicate that thoughtful reformulation of PEG based, therapeutic PICs with non-PEG alternatives can be accomplished without compromising the self-assembly of the PIC.